LANGUAGE AND THE NATION AS A PROBLEMATIC FIELD OF MODERN BELARUSIAN PROSE - Koshman, Pavel (Літературний процес: методологія, імена, тенденції, 2018)
The article notes the specifics of comprehension of the topic languages by modern Belarusian literature in the context of national identity and nation development. The author emphasizes the historical importance of the theses about the immediacy of the language and the need to protect it for the formation of Belarusian nation identity. The author notes the relevance of the idea of the value of the Belarusian language in the socio-cultural circumstances in the 20th–21st centuries. The defensive reaction of the national art of the word to the decline of the language is considered in dynamics. The author reveals the depth of comprehension of the modern state of the language problem in Fedorenko’s prose; he emphasizes the artistic efficiency of its representation is emphasized by F. Syvko through the establishment of the archaic fear of others and points out the prediction of the catastrophic consequences of linguistic nihilism in future artistic scenarios of A. Bakharevych, M. Martynovych, H. Severynets. The conclusion emphasizes the unity of writers’ position in the ideological justification of language value as a necessary condition for successful realization of the nation’s potential.